Influencia de la pedagogía de los valores en el comportamiento de los estudiantes de la unidad educativa “san camilo” del cantón Quevedo, Provincia de los Ríos del periodo lectivo 2014. 2015 - Pin Zamora, Carmen Annabel (2015)
Values are those qualities and moral virtues which are own and inherent in individuals that make up a society, what distinguishes them as persons trained to carry out any trade, office, study or profession, with excellence qualitative moral, ethics, the ethics and obviously in their own personal capacity. Values are goals for life, weekends are looking for in our daily activity; they put our hopes for happiness and the value of the people and of all reality, skills are the means for its achievement, i.e. personal stances by which we defend or acquire those values. The teaching profession has the difficult task of removing afloat each and every one of the values that students bring with them, should encourage them to conservation and implementation of those values, especially in the school environment that is the space in which to begin to work in groups, so you must implement the most essential values such as: respect, equality, solidarity, collaboration. In this way, will live in harmony with himself and with others.